2019
DOI: 10.1016/j.jcot.2018.10.005
|View full text |Cite|
|
Sign up to set email alerts
|

Improvising PRP for use in osteoarthritis knee- upcoming trends and futuristic view

Abstract: Platelet rich plasma (PRP) has clearly emerged offering a possible solution that could modify the disease process and offer symptomatic relief in early osteoarthritis of knee. Great efforts are underway to improve PRP products for use in knee osteoarthritis (OA). Upcoming research is focused on the ideal PRP type, dose, frequency of injection and mode of injection. The combination of PRP with biocompatible carriers/scaffolds like gelatin hydrogel and chitosan appear to be promising based on early in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
1
21
0
3
Order By: Relevance
“…Although, in our study, grade II OA knee flexion did not improve except in the patients who received a total of four PRP injections, the overall pain decreased in all grade II groups. This finding is directly in line with Dhillon et al's conclusion that PRP injections are an effective treatment for early-stage knee OA symptoms [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although, in our study, grade II OA knee flexion did not improve except in the patients who received a total of four PRP injections, the overall pain decreased in all grade II groups. This finding is directly in line with Dhillon et al's conclusion that PRP injections are an effective treatment for early-stage knee OA symptoms [ 28 ].…”
Section: Discussionsupporting
confidence: 89%
“…These approaches exploit the release of chemo-attractive, angiogenic, proliferative, and putatively pro-regenerative growth factors from PRP, making it suitable as a cell delivery vehicle [36]. The difficulty of controlling the growth factor and cytokine release in PRP makes it necessary to combine it with other molecules, mainly polyethylene glycol (PEG) or chitosan, in order to regulate this [30,33,34,[37][38][39]. Although PRP has shown its potency and capability in tissue regeneration, its experimental inconsistency and low reproducibility has meant that, in applications in which platelet-released growth factors are not crucial, PPP is generally used.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in addition to its anti-inflammatory effects, PRP may also have potential analgesic effects. Experimental studies have shown that in OA, PRP also affects synoviocytes, endothelial cells, and cells involved in cellular immunity (e.g., macrophages) [186,187]. Additionally, it has been shown that the concentration of growth factors, such as PDGF, β-FGF, VEGF, and IGF-1 increases at various time points within 96 h after the injection of PRP.…”
Section: Prp As Source Of Cytokinesmentioning
confidence: 99%